Analysis of The Effect of Service Quality on Customer Satisfaction (Study on Bank Danamon Singaraja Branch, Bali) - Putu Lidia Marini (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The study aims to determine the effect of service quality on customer satisfaction at Bank Danamon Singaraja Branch. The study used quantitative methods. Data collection techniques use literature studies, observations, and questionnaires. While the analysis techniques used are validity test, reliability test, Multiple Regression Analysis, t Test (Partial Test), F Test (Simultaneous Test). Referring to the research that has been done, it was concluded that the results of the Partial Test showed that the six variables, namely ability, attitude, appearance, attention, action and responsibility have a positive and significant influence. From the results of the Simultaneous Test shows that the six variables namely ability, attitude, appearance, attention, action and responsibility have a positive and significant influence. Of the six variables (ability, attitude, appearance, attention, action and responsibility) that have been tested, the most dominant variable affecting customer satisfaction at Bank Danamon Singaraja Branch is action. This is because of the magnitude of the actions given by employees to customers, it will provide satisfaction for depositor customers.